1990
DOI: 10.1136/ard.49.10.768
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of osteoarthritis of the knee.

Abstract: The repeatability of physical signs used to assess osteoarthritis of the knee has not been systematically examined. The within and between observer variation of 10 commonly used physical signs to determine osteoarthritis of the knee has been assessed here. The results obtained show variation in the repeatability of these signs. For those examining the tibiofemoral joints the repeatability was greater than for those examining the patellofemoral joint. It would therefore seem vital to take note of the repeatabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 6 publications
1
45
1
Order By: Relevance
“…The assessment for bony swelling, which is a key component of the ACR clinical diagnostic criteria for OA (10), was found to be highly reliable (grade A) in contrast to that observed in previous studies (11,12,15). Even with a change from a 3-point to a 4-point scale, reliability further improved after standardization, achieving a reliability coefficient of 0.97 (Table 3 and Figures 1 and 2).…”
Section: Cibere Et Almentioning
confidence: 58%
See 1 more Smart Citation
“…The assessment for bony swelling, which is a key component of the ACR clinical diagnostic criteria for OA (10), was found to be highly reliable (grade A) in contrast to that observed in previous studies (11,12,15). Even with a change from a 3-point to a 4-point scale, reliability further improved after standardization, achieving a reliability coefficient of 0.97 (Table 3 and Figures 1 and 2).…”
Section: Cibere Et Almentioning
confidence: 58%
“…However, the reliability of these and other signs by physical examination has not been evaluated comprehensively. A search of the literature revealed very few studies on the intra-and interrater reliability of the knee examination in OA (11)(12)(13)(14)(15) (Table 1). Although the data in Table 1 suggest apparently large between-study differences in reliability, a comparison of these values is not appropriate because they are not all based on the same measure of reliability and because the kappa statistic is very sensitive to differences in bias and prevalence.…”
mentioning
confidence: 99%
“…The AE5 scale of the vertical axis (except for standing sagittal measurements) was chosen to reflect the typical repeatability of other methods of assessing both sagittal [10] and coronal [24] knee alignment, including human variations in joint angle estimation [11]. However, it should be noted that considerably greater intra-observer estimates of knee flexion and extension angles have been reported, with critical differences between measurements of 7.1 to 21.4 [28]. The use of externally mounted markers and a motion capture system was not an entirely novel approach to measuring lower limb alignment.…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff of 5 degrees was used as an exclusion criterion in our study because the reliability of physical examination of laxity is low, with reported interobserver agreement of 0.55 (25). In our study participants the mean Ϯ SD knee laxity measurement was 2.7 Ϯ 3.0 degrees varus.…”
Section: Muscle Biopsy Samples (1 CMmentioning
confidence: 99%